Identifying and Prioritization the Factors Affective the Development of Industrial Clusters With Knowledge-based Companies - Javadj Mir; Hassan Dehghan dehnavi; Mozhde Rabbani (پژوهش‌های مدیریت عمومی)
AbstractOne of the new approaches to development is the development model of industrial clusters, which has an effective role in product innovation and competitiveness, and the changing needs and demands of customers, the rapid evolution of technology, increasing competition in the market, and increasing economic prosperity have caused companies in various industries to innovate and provide new products with increasing speed, efficiency and quality.Therefore, the current research was conducted with the aim of identifying and prioritizing factors affecting the development of industrial clusters with a sustainable development approach in Sistan and Baluchistan province. The research method is applied according to the purpose, and mixed (qualitative-quantitative) with an exploratory approach, according to the type of data; In this way, by using the meta-combination method in the field of industrial cluster development, research indicators were identified, the identified factors and components were weighed with the opinion of experts and based on the Fuzzy Hierarchy Analysis Process (FAHP) model, the factors were analyzed and combined, and Finally, prioritization was done.The statistical community in the qualitative part of the research included 17 experts and managers expert in production, who were selected non-probably and judgmentally, and the required information was collected from them using the Delphi method. In the following, in line with the validation of the research model, a research questionnaire was designed distributed among 116 sample members including managers, experts, and agencies active in the industry, and university faculty members in Sistan and Baluchistan province, who were randomly selected by stratified method. In order to analyze the data, the Fuzzy Hierarchy Analysis Model (FAHP) was used, and finally, the findings of the research showed that the most was the development of industrial clusters with a knowledge-based approach. The criterion of strategies and the two criteria of resources and superstructures are prioritized as the next important components.Introduction A review of the industrial cluster literature in recent decades shows that while many studies have examined industrial clusters in developed countries, we still lack comprehensive research that systematically addresses the dynamics and nature of cluster implementation in developing economies. Therefore, researchers are calling for more research to examine the transferability of current cluster theories in emerging markets and developing countries. This, in turn, emphasizes the role of localization and underlying factors in the performance of stimulus clusters and clarifying the issue in an applied scientific research is one of the most necessary and first steps of research. This research is an applied research that seeks to identify the factors affecting the development of industrial clusters with knowledge-based companies in Sistan and Baluchestan province.1) What are the factors affecting the development of industrial clusters in Sistan and Baluchestan province?2) What is their weighting using FAHP technique?so that managers can help entrepreneurs in their logical and balanced development.Case studyThe present research investigates and identifies and prioritizes the components of industrial cluster development with a focus on the sustainable development approach in Sistan and Baluchistan province. Therefore, the case study is selected industrial clusters of Sistan and Baluchistan province.Theoretical frameworkWith the formation and unceasing growth of knowledge-based companies, industries unavoidably create a cumulative effect after reaching a certain level or stage .When the effect of industrial agglomeration appears, industry growth will be stimulated and further optimization and upgrading will take place; thus the relevant industry chain will absorb this chain to achieve industry scale and efficiency (Lan, J., Chengjun, W. & Wei, Z., 2019), and finally, the phenomenon of industrial clusters is obtained Therefore, all countries in the world tend to research industrial clusters (Mayangsarit,L Novani,.S ,Hermawan,P., 2015). This, in turn, emphasizes localization and underlying factors in the development of new clusters.This research is also an applied research that seeks to identify the factors affecting the establishment of knowledge-based companies and the development of industrial clusters in Sistan and Baluchestan province, which help entrepreneurs in this regard. Therefore, to solve the problem, the method of hierarchical data analysis is used, based on which the importance of our subject is the study and development of industrial clusters. The above method was used to find subsets involved in the growth of industrial clusters. MethodologyThis is an applied mixed (qualitative-quantitative) research method. The qualitative research population included academic experts and practitioners in Sistan and Balochistan Province. 32 individuals were selected as research samples through the snowball sampling method. For the quantitative study, the research populations were 316 managers and brokerages active in the industry and governorship experts in Sistan and Balochistan Province. 116 individuals were selected as the qualitative research sample through a stratified random sampling method. Research qualitative data were collected through desk research and research background. Then, the effective factors were measured using a semi-structured interview with experts. Research quantitative data were also gathered through a researcher-made questionnaire. Research qualitative data were analyzed by the Meta-synthesis method. Further, the research model was verified by the Fuzzy Delphi Method. Then, the structural equation modeling was also used through SMART PLS (second version). Moreover, the indicators were prioritized using the FAHP technique.Discussion and resultsThe results of the research data analysis indicate that based on the studies conducted by the researcher, all the factors affecting the size of industrial clusters in Sistan and Baluchistan province were divided into three criteria, which are the priority of strategies, meta-structures and resources respectively. were classified. And the superstructures were divided into four sub-criteria: so that the application of strategies is prioritized with 4 sub-criteria, superstructures with 11 sub-criteria and resources with 7 sub-criteria.ConclusionSince various quantitative and qualitative factors are effective in the issue of locating industries, the use of multipurpose decision-making methods can be an effective strategy for this matter. The FAHP model is one of these methods that is widely used in locating and evaluating. Hierarchical analysis process is one of the most comprehensive systems designed for decision making with multiple criteria;Because this technique makes it possible to formulate the problem hierarchically by breaking down decision-making issues into decision-making elements. The importance and superiority of decision-making elements is determined by using the paired comparison method and according to its priority in the hierarchy. In this research, a specific application of this model was used in prioritizing the factors affecting the development of industrial clusters. The three main criteria of strategies, superstructures, and resources have been identified using past studies and researches, and each of them has been defined by several sub-criteria. So that the implementation of strategies is prioritized with 4 sub-criteria, superstructures with 11 sub-criteria and resources with 7 sub-criteria.According to the obtained results, finally, 10 factors affecting the development of industrial clusters were found to be more effective than other sub-criteria, and according to the findings of this research, recommendations can be made as follows:1- Strengthening credits and financial resources necessary for the development of industrial clusters and the implementation of development projects with the aim of increasing the competitiveness of industrial enterprises.2- Applying the cluster development model to increase the export capacity of small and medium enterprises and improve their value chain.3- Strengthening the legal position of industrial clusters in upstream documents and development plans in order to strengthen the export power of industrial enterprises.4- The use of network development tools, including horizontal and vertical networks, in the development of competitiveness and export of industrial enterprises.5- In a similar research, other possible factors affecting the development of industrial clusters should be investigated and their results should be combined with the results of the current research.